Récit de voyage à l’intérieur du Code criminel de 1892 où entre autres mention est faite des peines auxquelles ses transgresseurs s’exposent - Acosta, Fernando (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1995)
This article introduces some preliminary results from an ongoing research project on the history of the Canadian Criminal Code. These results focus mainly on two important aspects of the first version, promulgated in 1892, of this Code : the structure which has ruled over its construction (and which remains overwhelmingly untouched to this day), and the place of emprisonment in the overall framework of the sentencing provisions of the Code. A short explanation of some of the difficulties surrounding the identification and counting of the incriminatory statements in the Code's text precedes the presentation of these results. By way of conclusion, the author identifies one research avenue to which a detailed analysis of the legal texts in the field of penal law seems to point. It refers to the movement of widening and narrowing of the regulation power of the State, particularly in the fields of (de)criminalization and (de)penalization.